Anticancer and antimicrobial activities of supernatant fermented with lactobacillus sp. LAB1-or pediococcus pentosaceus LAB3 - Zainal, Nur Azida Wati (2017)
Dysbiosis, or imbalanced gut microbiota increases susceptibility of the host to chronic diseases such as colorectal cancer (CRC) and infectious diseases. Chemotherapy, which is widely used for the treatment of CRC and infectious diseases, is often compromised by side effects and drug resistance. This had led to increased demand for newer and safer alternatives that can prevent CRC and infectious diseases. Probiotics may serve as potential anticancer and antimicrobial agents. This present study had evaluated both anticancer and antimicrobial activity of Lactobacillus sp. LAB 1 and Pediococcus pentosaceus LAB3-fermented supernatant. Briefly, LAB 1 and LAB3 were cultured in MRS broth and incubated at 37°C overnight. The cultures were centrifuged and supernatant was collected by filter sterilisation. The LAB 1- and LAB3-fermented supernatant was tested against Escherichia coli and Staphylococcus aureus by using the Broth Microdilution Assay. Minimum inhibitory concentration (MIC) was determined by observing for the lowest concentration whereby the visible growth of pathogen was inhibited. Ampicillin was included as positive control. The anticancer activity of LAB!- and LAB3-fermented supernatant against human colorectal carcinoma cell line (HCTI 16) was assessed by using the SRB assay. HCT116 were treated with 20 µL of the LAB fermented supernatant (0.1 %-4%) and incubated for 72 hours. 5-FU was included as positive control. Results obtained were used to plot the dose-response curves.